Diversities of Sexual Activities and Correlates of Safe Sex Practices Among Adolescents in Plateau State, Nigeria - Envuladu, Esther Awazzi; Massar, Karlijn; de Wit, John B. F. (Frontiers in Reproductive Health, 2021)
Background: Unsafe sex, particularly, condomless sex exposes adolescents to sexual and reproductive health risks. This study aimed to assess the sexual experiences and to determine the most important covariates of sexual activity and consistent condom use among adolescents in Plateau State, Nigeria. Methods: A cross sectional survey was conducted among 428 adolescents selected from 6 LGAs through a multistage sampling technique. The data was analyzed using the IBM Statistical package for Social Sciences (SPSS) version 23, multiple logistic regression was conducted to determine the covariates of sexual activity and condom use. Results: About one third (38%) of the adolescents were sexually active, 5.7% had same sex partners, 70% had more than one sexual partner and majority (72.4%) were not consistently using condom during sex. Logistic regression results showed that older adolescents (OR = 5.73; CI = 3.72–8.12; p = 0.001) and out of school adolescents (OR = 2.68; CI = 1.79–4.00; p = 0.001) were more likely to be sexually active, while multivariable logistic regression analysis showed age (AOR = 0.33; CI = 0.12–0.90; p = 0.031) and gender as important covariates of being sexually active, (AOR = 6.29; CI = 3.18–12.44; p = 0.001). Inconsistent condom use was more likely among adolescents; with lower education, (OR = 2.14; CI = 1.19–3.85; p = 0.011), having sex with older partners (OR = 0.61; CI = 0.42–0.90; P = 0.013) and with low awareness of SRH issues (OR = 2.08; CI = 1.02–4.22; p = 0.044). The multivariable logistic regression however, showed gender, being male (AOR = 0.43; CI = 0.006–3.09; p = 0.023) as covariate of consistent condom use. Conclusion: Most sexually active adolescents had multiple sexual partners, some had same sex partners and majority were not consistently using condom. Older adolescents and those out of school were more likely to be sexually active. Awareness of SRH issues significantly influenced condom use while gender, specifically being male, was the independent covariate for being sexually active and for consistent condom use. We recommend sexual health intervention targeted at adolescents. In addition, gender should be mainstreamed into adolescent sexual and reproductive health programmes.